DISCOVERY OF POLYGALACTURONASE PRODUCING BACILLUS TEQUILENSIS STRAIN ARMATI USING 16S rRNA GENE SEQUENCING - C, AARTI; A, KHUSRO (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: To identify a novel strain of polygalacturonase producing Bacillus tequilensis from poultry farm. Methods: Poultry feces sample was serially diluted, and the pure isolate was subjected to morphological tests, biochemical tests, genomic DNA isolation, polymerase chain reaction amplification, amplicon purification and 16S rRNA gene sequencing. The strain was screened for polygalacturonase production using plate assay method. The nucleotide sequences obtained from the isolate were subjected to BLAST tool for the pairwise alignment. RNA secondary structure was predicted through RNAStructure Web Server. Multiple antibiotic resistance (MAR) index was determined against six antibiotics through disc diffusion method. Phylogenetic trees were inferred using the neighbor-joining algorithm in Molecular Evolution Genetic Analysis software version 4.0. Results: B. tequilensis strain ARMATI showed the production of polygalacturonase. MAR index of this novel strain was found to be zero. RNA secondary structure with a minimum free energy of âˆ’281.40 kcal/mol was obtained. Phylogenetic tree of Bacillus 16S rRNA genes separate each Bacillus according to their taxonomic positions and were supported statistically. Conclusion: The present investigation clearly indicates the isolation, molecular characterization and sequence analysis of B. tequilensis strain ARMATI from poultry farm, and industrial application of this novel strain for the production of the enzyme. Keywords: Bacillus tequilensis, Multiple antibiotic resistance index, Polygalacturonase, Phylogenetic tree, RNA secondary structure, RNAStructure Web Server.